Atitudes linguísticas: um estudo na localidade paranaense de Guaíra - Fungueto, Anelí Divina (2021)
The thesis “Linguistic attitudes: a study in the city of Guaíra in Paraná” is part of a set of sociolinguistic and dialectological research developed based on the theme of beliefs and linguistic attitudes. In this research, an investigation is carried out on the linguistic manifestations of male speakers from the city of Guaíra, western region of the State of Paraná, Brazil. The investigated location has a socio-historical and geographic reality that facilitated contact between different languages. The population of the region by waves of immigrants of different ethnicities, the border with Mato Grosso and cities in Paraná and the border with Paraguay, a neighboring country, allowed for the development of a peculiar multilingualism, giving rise to a study involving beliefs and linguistic attitudes, thus providing a portrait of how a context of languages in contact was constituted. Based on the assumption that language and age groups are related, studies developed in the fields of Sociolinguistics, Social Psychology, Ethnography of Communication and Sociology of Language were sought as a theoretical and methodological basis. The corpus was collected by the Linguistic Beliefs and Attitudes Project: a study of the relationship between Portuguese and contact languages (Aguilera, 2009) from interviews with 18 informants, selected from the variables: a) age groups: 18 to 30 years, 31 to 50 years, 51 to 70 years; b) education levels: elementary, middle and higher; and c) male and female sex. The quiz elaborated for the collect contained questions adapted to the sociolinguistic and cultural reality of the investigated community, with the objective of evaluating the linguistic attitudes in the performance of the speakers in relation to the languages in contact. For this research, sixteen questions were selected from the CAL project and addressed to six male informants from Age Group 1 and Age Group 3. The analysis of the corpus follows the mentalist approach that understands attitude as a human behavior formed by the components: cognitive, affective and conative. The results showed that the informants manifested prejudices or appreciations influenced by geographic and socio-historical factors.